Kompetensi Abad 21 Sebagai Bekal Menghadapi Tantangan Masa Depan - Asri, Indra Himayatul; Lasmawan, I Wayan; Suharta, I Gusti Putu (Universitas Hamzanwadi, 2023)
Indeed, the world of education and learning develops with the changing times. Life in the 21st century demands various skills that must be mastered by a person, so it is hoped that education can prepare students to master these various skills in order to become successful individuals in life. In the 21st century, learning is not only cognitive-centered and students only memorize but in the era of the industrial revolution 4.0 students are required to be able to compete with other countries through creative thinking skills, critical thinking and problem solving (critical thinking and problem solving). problem solving), communicate (communication), and collaborate (collaboration) or commonly referred to as 4C. competencies that must be possessed by students must of course be able to adapt to the development of the 21st century so that with these competencies they will be able to answer all challenges in the future. Important skills in the 21st century are still relevant to the four pillars of life which include learning to know, learning to do, learning to be and learning to live together. Each of these four principles contains specific skills that need to be empowered in learning activities, such as critical thinking skills, problem solving, metacognition, communication skills, collaboration, innovation and creation, information literacy, and various other skills.